Workload as A Cause of Occupational Stress Among Registered Staff Nurses - Ghulam Abbas Panhwar; Pir Bux Jokhio; Humaira Wagan; Husun Banu Channar (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective: To evaluate the sources of occupational stress related to workload among registered staff nurses. Methods: A cross-sectional study was conducted among 100 staff nurses.  "Hospital  consultants,  job stress & satisfaction questionnaire (HCJSSQ)" was applied for data collection purpose.  The  questionnaire was formulated by an appropriate selection of questions and validated  by  5  experts  (one general administrator, two physicians, one nursing  superintendent,  and  one  human  resource  man-  ager). The study was carried out during February-July 2016. The questionnaire consisted of 08 questions on sources of stress related to workload. Results: All the invited nurses agreed to participate.  The mean age of the selected sample was 32.29  years and SD ± 7.025. The analysis of the data revealed that 'having an inadequate staff to do the job'     was the biggest stressor followed by 'being  on  on-call  and  'providing  patient  care  within  multidisciplinary teams  as  2nd  and  3rd  stressors.  'Feeling  under  pressure  to  meet  deadlines',  'too  great magnitude of overall work', 'having inadequate  equipment  to  do  job  properly',  'disturbance  of  home life due to long hours duty' and   'being unable to cure patients' were identified as 4th, 5th, 6th, 7th, and 8th number stressors respectively. Conclusion: Nurses are facing various types of stressors, which may affect organizational culture and a factor for low-quality care for patients as well as the individual wellbeing of a  staff  nurse.  These  stressors should be handled carefully on a priority basis by proper workload management, availability of facilities, good pay scale, reward system, initiate occupational  health  education  or  support  to  continue education.